Apoptosis-inducing proteins with reduced expression in breast cancer: A review article - Mohammad Mehdi Khaleghi; Faezeh Rouhi; Kourosh Eslami; Fatemeh Shafiee (Biochemistry and Biophysics Reports)
Breast cancer is considered one of the most abundant malignancies with high morbidity and mortality. Traditional cancer treatments possess various weaknesses, including a lack of specificity and numerous side effects. Novel cancer therapies aim to overcome the shortcomings of traditional therapies and offer more efficient and safe treatments. Designing and identifying novel proteins that can practically and specifically inhibit tumors by inducing apoptosis can interest researchers in this field. This review discusses recent studies on the use of four promising proteins, KAI1, Apoptin, BIF-1, and DFF-40, for breast cancer treatment. This study also focuses on alterations in the expression of the androgenic proteins and novel strategies for better penetration and delivery of these proteins. Lastly, prospects for protein-based targeted cancer therapy and future studies in this field are highlighted.